An Effort to Increase the Role of Halal Tourism: West Nusa Tenggara Islamic Center - Uwi Murtayadi; Muhammad Azizurrohman; Supiandi Supiandi (Journal of Economics Research and Social Sciences, 2022)
Recently, religious tourism has attracted the attention of various parties because of the high interest of Muslim tourists. West Nusa Tenggara (NTB) is one of the provinces that carry religious or halal tourism. It was proven by attaining the halal tourism destination award by the West Nusa Tenggara Islamic Center in 2015. However, the West Nusa Tenggara Islamic Center still lacks development and literacy, especially tourism. Therefore, the motivation of this research is to find alternative strategies that might be used for the development process and increase literacy. By interviewing four respondents, the authors uncovered alternative strategies using SWOT analysis. The five strategies might be beneficial: collaborating with stakeholders, creating new attractions, marketing destinations, improving service quality, and strengthening the destination concept.